Polygonal Complexity Counting Classes - Nasser, Nasser (Latakia University Journal -Engineering Sciences Series, 2018)
In this work we introduce new counting classes defined by special sets of natural number like Triangular, Perfect Square, Pentagonal and generally K-gonal numbers. We shall see that NP is a subclass of all complements of K-gonal classes and all K-gonal classes are subclasses of a class defined by only perfect square numbers. صفوف التعقيد العدّية المضلعة في هذا العمل تمّ تعريف صفوف تعقيد عدّية جديدة اعتمادا على مجموعات جزئية من مجموعة الأعداد الطبيعية كالأعداد المثلثية 3-gonal والمربعة 4-gonal والمخمسة5-gonalوعموما الأعداد المضلعة K-gonal numbers وسنبين أنّ الصف NP هو صف جزئي من مجموعة متممات الصف المولد بالمجموعةK-gonal وأنّ الصفوف التي تعرفها المجموعات K-gonal هي صفوف جزئية من الصف الذي تعرفه مجموعة الأعداد المربعة فقط